2016
DOI: 10.1097/md.0000000000002812
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Neck Hematoma After Thyroidectomy

Abstract: To identify risk factors for post-thyroidectomy hematoma requiring airway intervention or surgery (“wound hematoma”) and determine post-thyroidectomy time to intervention.Post-thyroidectomy hematoma is rare but potentially lethal. Information on wound hematoma in a nationwide clinical setting is scarce.Using the Japanese Diagnosis Procedure Combination database, we extracted data from records of patients undergoing thyroidectomy from July 2010 to March 2014. Patients with clinical stage IV cancer or those with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 19 publications
(30 reference statements)
2
35
2
Order By: Relevance
“…Unlike previous studies suggest that postthyroidectomy haemorrhage increased in patients with malignant pathology (2,13,19,21) or benign pathology (11,12,15,18). We were surprised to find that there was no association between the pathological diagnosis and post-thyroidectomy haemorrhage (OR = 1.07, 95% CI = 0.89-1.28, P = 0.46).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Unlike previous studies suggest that postthyroidectomy haemorrhage increased in patients with malignant pathology (2,13,19,21) or benign pathology (11,12,15,18). We were surprised to find that there was no association between the pathological diagnosis and post-thyroidectomy haemorrhage (OR = 1.07, 95% CI = 0.89-1.28, P = 0.46).…”
Section: Discussionmentioning
confidence: 65%
“…Flow chart of the meta-analysis. (2,4,6,11,12,17). After the analysis, we concluded that the use of antithrombotic agents for thyroidectomy patients, regardless of dosage, was associated with post-thyroidectomy haemorrhage (OR = 1.96, 95% CI = 1.55-2.49, P < 0.00001) ( Fig.…”
Section: Figurementioning
confidence: 87%
See 1 more Smart Citation
“…Mechanical airway obstruction due to tissue edema or hematoma is a well-recognized surgical complication after various neck surgeries including thyroidectomy [ 138 ] and CEA [ 139 , 140 ]. Particularly during CEA, surgical procedures including dissection, traction, and retraction can injure the facial nerve, hypoglossal nerve, the vagus nerve including its branches (recurrent and superior laryngeal nerves), or glossopharyngeal nerve within the operative field [ 141 – 144 ].…”
Section: Safety Issues Related To Cervical Plexus Blocksmentioning
confidence: 99%
“…Although thyroid surgery is a relatively safe procedure, it may be associated with some clinically concerning postoperative complications, including postoperative cervical hematoma, incision infection, hypocalcemia, and in some cases vocal cord paralysis. Of these, the development of postoperative cervical hematoma, although rare (incidence: 0.43–6.54%) [227], may lead to symptoms of compression causing airway obstruction, respiratory distress, or even death due to suffocation.…”
Section: Introductionmentioning
confidence: 99%